Status of Agricultural Stagnation in Nepalese Economy: A Descriptive Analysis - Khatri, Bishnu Bahadur; Timsina, Tirtha Raj (NUTA Journal, 2023)
Agriculture contributes as a means of survival for more than half of the total population in Nepal, the production and productivity of the sector remain stagnant during the recent years. In this connection, the aim of this research paper is to find out the current status and causes of agricultural stagnation in Nepal. This is a review based descriptive research paper having quantitative information. Secondary data are used to accumulate the information and describe the result depending on the research objective. The result of this paper revealed that there are some factorsuch as technological backwardness, absentee landlords, migration, and attraction of the youth for remittance income abroad are responsible for agricultural stagnation. Mitigation of such factors through the intensification and modernization for agricultural transformation is well accepted measure to enhance agricultural outcomes by which the problem of agricultural stagnation would be resolved.